A simplified chemorheological model of viscosity evolution for solvent containing resol resin in RTM process. Issue 36 (1st June 2017) - Yi, Xiaolin; Kuang, Xiao; Kong, Lei; Dong, Xia; Feng, Zhihai; Wang, Dujin
ABSTRACT: The solvent content‐dependent chemorheology of the solvent containing resol resin for resin transfer molding (RTM) was investigated. The curing behavior of the resol resin was studied by in situ Fourier transform infrared spectroscopy together with rheology tests. The chemorheological behavior of resol resins with a series of solvent contents was measured under isothermal conditions. The four parameters of empirical dual‐Arrhenius equation regarding isothermal resin viscosity and reaction rate constant were found to be functions of the solvent content. A simplified chemorheological model involving only three parameters of curing temperature, time, and solvent content was first established to facilely describe the viscosity during precuring process. The simulated viscosity results during isothermal curing process agreed well with the experimental data which shows the simplified chemorheological model can be utilized to describe the viscosity evolution and offer guidance for optimizing the injection process and improving the design flexibility of RTM process. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45282. Abstract :